Determinants of Service Quality, Social Media, and Timeliness Towards Institutional Image Through Customer Satisfaction (Case Study at DPMPTSP Bogor District) - Mochammad Noor Taufik (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
This study aims to analyze the improvement of institutional image through customer satisfaction influenced by service quality, social media, and punctuality. By using the Structural Equation Modeling (SEM) method through the LISREL 8.80 program, it was found that the variables of service quality (X1), social media (X2), and punctuality (X3) significantly affect customer satisfaction (Y) and institutional image (Z). The dominant dimensions of each variable are reliability for service quality, participation in social media, and accuracy of the service process for punctuality. In addition, customer satisfaction has a significant influence on institutional image, with the dimension of conformity to expectations as the most dominant aspect. The results of the analysis show that social media is the most dominant variable in influencing customer satisfaction, while customer satisfaction is the main factor in improving institutional image.